1995
DOI: 10.1099/0022-1317-76-9-2361
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of poliovirus B and T cell epitopes presented by hybrid porcine parvovirus particles

Abstract: We have analysed the potential capacity of hybrid porcine parvovirus (PPV) capsids to present foreign epitopes to the immune system. Foreign sequences were introduced into the N and C termini of PPV VP2, which was previously shown to assemble spontaneously into parvovirus-like particles. The integrity of the C terminus was shown to be essential for preserving the structure of the capsid and therefore could not be used for epitope fusion. In contrast, insertion of sequences corresponding to T and B cell poliovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Very recently, the existence of cross-presentation and crosspriming as general, physiological processes to induce CD8 ϩ T cell response has been doubted (76) on the basis of the lack of convincing in vivo solid experimental evidence. Previous studies have clearly showed that exogenous PPV-VLPs can induce a protective antiviral response, based on the induction of a high frequency of CTLs of high affinity (12,13,16,77). The evidence presented in this report clearly establishes that PPV-VLPs processing by DCs involves cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the existence of cross-presentation and crosspriming as general, physiological processes to induce CD8 ϩ T cell response has been doubted (76) on the basis of the lack of convincing in vivo solid experimental evidence. Previous studies have clearly showed that exogenous PPV-VLPs can induce a protective antiviral response, based on the induction of a high frequency of CTLs of high affinity (12,13,16,77). The evidence presented in this report clearly establishes that PPV-VLPs processing by DCs involves cross-presentation.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed an Ag delivery system based on nonreplicative, recombinant parvovirus-virus-like particles (PPV-VLPs) formed by the self-assembly of the VP2 capsid protein of porcine parvovirus (PPV) (12,13). The VP2 protein (14), carrying foreign CD8 ϩ T cell epitopes, self-assembles into 25-nm VLPs after expression in insect cells (13).…”
mentioning
confidence: 99%
“…These vectors were used to express the recombinant capsid proteins MMV rVP2 and MPV rVP2 in insect cells. It is known that many parvovirus recombinant VP2 proteins, including MMV rVP2, assemble into virus-like particles (VLPs) when expressed in baculovirus expression systems (6,8,16,24,27). To determine if baculovirus-expressed MMV rVP2 or MPV rVP2 proteins self-assembled into VLPs, we subjected clarified supernatants of insect cells infected with the MMV-rVP2 Bac vector or the MPV-rVP2 Bac vector to CsCl gradient ultracentrifugation.…”
Section: Rvp2mentioning
confidence: 99%
“…Our data illustrate that the sequence Trp-Thr-Ser is detrimental for PPV VP2 expression and for capsid formation. A similar effect, although less evident, was previously observed for the insertion of two CD4 + T-cell epitopes, polio C3:T (Sedlik et al, 1995) and PreST from hepatitis B (Lo-Man et al, 1998), which also contain a Trp residue. In these cases, the particles with an altered morphology assembled with low efficiency.…”
Section: Discussionmentioning
confidence: 55%
“…Several constructs of the OVA epitope with different flanking sequences or different lengths were prepared (Table 1). Plasmid pPPV29mod (Sedlik et al, 1995), which contains a unique XhoI restriction site immediately downstream of the initiation codon of the VP2 gene, was the starting material for the cloning experiments. The plasmid was linearized with XhoI (MBI Fermentas) and treated with alkaline phosphatase (Roche Molecular Biochemicals).…”
Section: Methodsmentioning
confidence: 99%